Stalked in the Catacombs - Doyle, Peter Reese; Nang Chan Yeema (Colorado Springs, CO USA Focus on the Family Publishing, 1993)
Mark and Penny Daring and their friend David Curtis are in Paris for a holiday and act as couriers for sensitive information. When they are attacked on a tour of the catacombs under the city, they become separated and must find their way back alone.
Keywords: Adult Fiction